The Role of a Chabot Personality in the Attitude of Consumers Towards a Banking Brand - Palomino-Navarro, Natalia (2022)
In recent years, it has been seen that brands have opted to implement chatbots as part of their digital customer service channels, especially since they can be hosted on social networks such as Facebook Messenger and WhatsApp. Although the use of this has become widespread, users perceive them as inefficient and of little credibility. The design of the personality of a chatbot arises as an alternative for the brand to generate a more human interaction with the user and show its brand values to generate a positive experience. In addition, a projected growth of the business value of chatbots for brands of 3.9 trillion dollars is estimated by 2022. For this reason, knowing how brands can rely on the correct implementation of the personality of a chatbot creating a positive influence on its users is important in a growing industry. The present research seeks to know how the personality of the chatbot influences the formation of consumer attitudes towards a brand. This exploratory study used a qualitative methodology of phenomenological design with young adults from Lima. Subsequently, it was analyzed through descriptive coding. It was found that the social dynamics, the social role and the physique of the chatbot are the aspects that influence the attitude towards the brand and generate a feeling of trust and closeness between the chatbot and the brand.